An examination of the extent to which reckless conduct precipitated the contemporary global financial crisis and an ensuing evaluation of existing and potential appropriate sanctions and offences for deemed reckless conduct in respect of corporate governance and with an express focus on the financial sector - Geraghty, Rachel (Trinity College (Dublin, Ireland). School of Law, 2016)
The curious question of further expanding legal provisions to deter against reckless conduct and excessive risk-taking, having regard to the financial sectors and indeed corporate governance generally, is undoubtedly one which would be met with controversy and opposition. Nonetheless, the potential need for such provisions is something that has been considered by both the Law Reform Commission and the Office of the Director of Corporate Enforcement in Ireland. Fundamentally at odds with the essential spirit of entrepreneurial behaviour and capitalism, there is a certain reluctance to regulate risk in circumstances whereby risk is inherent. However, particularly taking account of the recent economic epoch that we are slowly recovering from, it is critical to look back on the conduct of the past; particularly with a view to attenuating future prospective financial crises. One cannot ignore the potential role that excessive risk-taking and perhaps even reckless conduct, most significantly in the banking and securities sectors, played in the global financial crisis of 2008. Hence, the potential for legislative and regulatory reform and indeed, how such might be received and permitted to operate in practise, must be examined. While there is an undoubted paucity of academic commentary on the area, it is hoped that this endeavour may be of some contribution. The curious question of further expanding legal provisions to deter against reckless conduct and excessive risk-taking, having regard to the financial sectors and indeed corporate governance generally, is undoubtedly one which would be met with controversy and opposition. Nonetheless, the potential need for such provisions is something that has been considered by both the Law Reform Commission and the Office of the Director of Corporate Enforcement in Ireland. Fundamentally at odds with the essential spirit of entrepreneurial behaviour and capitalism, there is a certain reluctance to regulate risk in circumstances whereby risk is inherent. However, particularly taking account of the recent economic epoch that we are slowly recovering from, it is critical to look back on the conduct of the past; particularly with a view to attenuating future prospective financial crises. One cannot ignore the potential role that excessive risk-taking and perhaps even reckless conduct, most significantly in the banking and securities sectors, played in the global financial crisis of 2008. Hence, the potential for legislative and regulatory reform and indeed, how such might be received and permitted to operate in practise, must be examined. While there is an undoubted paucity of academic commentary on the area, it is hoped that this endeavour may be of some contribution.
Keywords: Law, LL.M.; LL.M. Trinity College Dublin